Scaling climate-smart agriculture: Co-creating business models in the supply and finance chains in Nyando, Western Kenya - Wattel, Cor; Gathiaka, John; Mulwa, Richard; Asseldonk, Marcel van; Wesenbeeck, Lia van; Oostendorp, Remco; Recha, John W.M.; Radeny, Maren A.O.; Bosselaar, Jonne (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In the context of Nyando, with very small land sizes and subsistence agriculture, it is hard to envisage a large investable CSA portfolio. Smallholder farmers and commercial parties tend to see each other as risky partners in business. Building trust and long-term partnerships are the key to success of upscaling CSA investments. From the viewpoint of commercial players, Nyando is considered competitive in drought-resistant crops (sorghum and cassava). Seeds and fertilizers for these crops are an interesting market for the input suppliers. Milling sorghum into flour could add value to their business. It might be profitable for smallholder farmers to turn their sorghum food crop into a cash crop. This business model could be further enhanced with warehousing and with contracts with off-takers, but this requires certain conditions to be met for it to be successful. In the context of Nyando, modest increases in smallholder farmer finance are possible, through two channels. Firstly, through linkages between banks and community savings groups. And secondly, where farmers have access to marketing contracts with off-takers.